2018
DOI: 10.2478/subboec-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

The FDI-Growth Nexus in South Africa: A Re-Examination Using Quantile Regression Approach

Abstract: This study sought to contribute to the growing empirical literature by investigating the effects of FDI on per capita GDP growth for South Africa using time series data collected between 1970 and 2016. Compared to the majority of previous studies, we use quantile regressions which investigates the effects of FDI on economic growth at different distributional quantiles. Puzzling enough, the empirical results show that FDI has a negative influence on welfare at extremely low quantiles whereas at other levels thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 58 publications
4
12
1
Order By: Relevance
“…This claim is consistent with existing studies including Pradhan et al (2019) and Sarkodie and Strezov (2019). Contrary to this view, Goh et al (2017) and Khobai et al (2018) state that FDI inflow is exploitative and could be regarded as a non-catalyst to economic development. Goh et al (2017) and Khobai et al (2018) concluded that the perceived impact of FDI inflow is more of a fallacy rather than a reality.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…This claim is consistent with existing studies including Pradhan et al (2019) and Sarkodie and Strezov (2019). Contrary to this view, Goh et al (2017) and Khobai et al (2018) state that FDI inflow is exploitative and could be regarded as a non-catalyst to economic development. Goh et al (2017) and Khobai et al (2018) concluded that the perceived impact of FDI inflow is more of a fallacy rather than a reality.…”
Section: Introductionsupporting
confidence: 91%
“…Contrary to this view, Goh et al (2017) and Khobai et al (2018) state that FDI inflow is exploitative and could be regarded as a non-catalyst to economic development. Goh et al (2017) and Khobai et al (2018) concluded that the perceived impact of FDI inflow is more of a fallacy rather than a reality. However, the recent unexpected fluctuation in FDI and the extent to which it impacts sub-Saharan Africa (SSA) countries require empirical investigation.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, (Flora and Agrawa 2014;Pandya and Sisombat 2017;Mehic et al 2013). Goh et al (2017) submitted that on the overall, there is no evidence of the positive impact of FDI in the long-run for the Asian economies, confirming the work of Mah (2010) and Khobai et al (2017). Bezuidenhout (2009) proved that the perceived impact of FDI on economic growth is a fallacy for the southern Africa region.…”
Section: Literature Reviewmentioning
confidence: 57%
“…These distinctive characteristics informed this study with the intention of adopting the TY Granger causality test using one functional model to achieve the following objectives: first, carry out a country-specificstudy on the FDI-led growth hypothesis because ofno consensus in the empirical literature (Guimaraes et al 2000;Fedderke & Romm 2006;Shahbaz et al, 2013;Sunde 2017;Khobai et al 2017), especially for South Africa. Second, Nielsen et al (2017) argued that industrialization, infrastructure improvement and the seat of power (government) that characterizes the urban centre could serve as a catalyst for attracting FDI inflows.The study opines that urban conglomeration with improved infrastructures is an agent for attracting FDI inflow into the host country, that is, urban centres are attractive sights for the inflow of new investors into the host country.…”
Section: Introductionmentioning
confidence: 99%